Landscape function analysis as a base of rural development strategies - Filepné Kovács, Krisztina; Dancsokné Fóris, Edina; Valánszki, István (Journal of Environmental Geography, 2017)
Research on ecosystem services and landscape functions are highly important in landscape ecology, landscape planning and open space design. The terms of ecosystem service and landscape function have been evolved parallel to each other in the scientific literature but have different focus. The term of landscape functions evolved from the scientific field of landscape ecology; it reflects the goods and services provided by regions, landscapes where the cultural, economic factors are important as well. As a framework assessment method with additional economic assessment, a landscape function analysis could be an additional tool of rural development, as it gives a complex analysis of multiple aspects, thus it is highly appropriate to explore, analyze the potentials, resources and limits of landscapes and land use systems. In the current research a landscape function analysis was compared with the rural development strategies in Hungarian micro-regions. We focused on the level of landscape functions and the objectives of the rural development strategies of the study areas. The local development strategies do not focus on territorial differences nor potentials evolving from natural, cultural resources or local constrains. The only exception is tourism development, where in some cases there is a holistic spatial approach which intends to develop the region as a whole.